2016
DOI: 10.17221/110/2015-pps
|View full text |Cite
|
Sign up to set email alerts
|

Natural prevalence of entomopathogenic fungi in hibernating pupae of Cameraria ohridella (Lepidoptera: Gracillariidae) and virulence of selected isolates

Abstract: Schemmer R., Chládeková P., Medo J., Barta M. (2016): Natural prevalence of entomopathogenic fungi in hibernating pupae of Cameraria ohridella (Lepidoptera: Gracillariidae) and virulence of selected isolates. Plant Protect. Sci., Spontaneous infection of hibernating Cameraria ohridella pupae by entomopathogenic fungi was monitored at two localities of south-western Slovakia and efficacy of selected fungal isolates against the pupae was evaluated in laboratory. Natural prevalence of fungal infection in pupal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Studies on the effectiveness of B. pseudobassiana in insects of the order Lepidoptera are few. Of these, Schemmer et al (2016) reported that six different B. pseudobassiana strains were applied to Cameraria ohridella Deschka & Dimić (Lepidoptera/Gracillariidae), and all strains caused 100% mortality on the tenth day. Gürlek et al (2018) stated that B. pseudobassiana caused death in Cydia pomonella Linnaeus (Lepidoptera/ Tortricidae).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effectiveness of B. pseudobassiana in insects of the order Lepidoptera are few. Of these, Schemmer et al (2016) reported that six different B. pseudobassiana strains were applied to Cameraria ohridella Deschka & Dimić (Lepidoptera/Gracillariidae), and all strains caused 100% mortality on the tenth day. Gürlek et al (2018) stated that B. pseudobassiana caused death in Cydia pomonella Linnaeus (Lepidoptera/ Tortricidae).…”
Section: Discussionmentioning
confidence: 99%
“…The most widely distributed fungus in insects populations B. bassiana was registered in dead larvae or pupae of C. ohridella (Draganova and Tomov 2000b;Prenerová et al 2008;Metla et al 2013). Another fungal species isolated from the horse chestnut leafmining moth were Isaria fumosorosea Wize (Zemek et al 2007;Schemmer et al 2016), B. pseudobassiana S.A. Rehner & Humber and Isaria farinosa (Holmsk.) Fr.…”
Section: Discussionmentioning
confidence: 99%
“…Fr. (Schemmer et al 2016), fungi belonging to the genera Aspergillus, Hirsutella, Metarhizium and Lecanicillium (Metla et al 2013). As Schemmer et al (2016) reported the mean mortality rate of pupae due to fungal infection was low and it reached 4.20%; however, the level of mortality varied depending upon collecting date, locality, year, and fungus.…”
Section: Discussionmentioning
confidence: 99%
“…However, information on C. ohridella-related fungal entomopathogens remains scarce, and most investigations of fungi involved in moth mortality have been performed in a single country only, namely in the Czech Republic [26][27][28][29][30]. Fungi belonging to the genera of known fungal entomopathogens (Beauveria Vuill., Lecanicillium W. Gams and Zare, Metarhizium Sorokin, and Paecilomyces Bainier) were isolated from C. ohridella habitat and some strains showed entomopathogenic activity against pupae and moth caterpillars [31][32][33][34][35]. Unfortunately, information on fungi virulence throughout moths' developmental stages remains scarce.…”
Section: Introductionmentioning
confidence: 99%